2015
DOI: 10.1080/02678292.2015.1070925
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to measure the twist elastic constant of a nematic liquid crystal

Abstract: We demonstrate a simple method for measuring the twist elastic constant (K 22 ) of a nematic liquid crystal (LC). By adding some chiral dopant to an LC host, the LC directors rotate 180°in a homogeneous cell, which is known as 180°super-twisted nematic (STN) cell. By preparing two such STN cells with different chiral concentrations and measuring their Fréedericksz threshold voltages, we can obtain the K 22 and helical twisting power simultaneously. In the whole process, there is no need to measure the pitch le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
(45 reference statements)
4
32
0
Order By: Relevance
“…Xiang et al [6] explored the very same dimer CB7CB at the temperature 106 0 C and found that 11 K =5.7 pN and 22 K = 2.6 pN, i.e., 11 22 / 2.2 KK  , as expected; for CB7CB doped with 1wt % of the chiral dopant S811, 33 K was determined to be 0.3 pN. Finally, Parthasarathi et al [18] measured 33 K by the extrapolation approach similar to that of Yun et al [16] but arrived at a very different conclusion that 33 K of pure CB7CB is monotonically increasing as the sample is cooled down. It is only when CB7CB is mixed with a monomer 7OCB in some proportions that 33 K shows a non-monotonous behavior, first increasing and then decreasing as the temperature is lowered from the clearing point ( NI T ).…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Xiang et al [6] explored the very same dimer CB7CB at the temperature 106 0 C and found that 11 K =5.7 pN and 22 K = 2.6 pN, i.e., 11 22 / 2.2 KK  , as expected; for CB7CB doped with 1wt % of the chiral dopant S811, 33 K was determined to be 0.3 pN. Finally, Parthasarathi et al [18] measured 33 K by the extrapolation approach similar to that of Yun et al [16] but arrived at a very different conclusion that 33 K of pure CB7CB is monotonically increasing as the sample is cooled down. It is only when CB7CB is mixed with a monomer 7OCB in some proportions that 33 K shows a non-monotonous behavior, first increasing and then decreasing as the temperature is lowered from the clearing point ( NI T ).…”
Section: Introductionmentioning
confidence: 58%
“…The latter result is somewhat surprising, as 11 22 / KK is expected to be larger than 2 in CB7CB, since this material does exhibit the Ntb phase rather than a splay-bend nematic, as demonstrated in the freeze-fracture transmission electron microscopy studies by Borshch et al [4] and by the resonant carbon soft X-ray scattering by Zhu et al [17]. Xiang et al [6] explored the very same dimer CB7CB at the temperature 106 0 C and found that 11 K =5.7 pN and 22 K = 2.6 pN, i.e., 11 22 / 2.2 KK  , as expected; for CB7CB doped with 1wt % of the chiral dopant S811, 33 K was determined to be 0.3 pN. Finally, Parthasarathi et al [18] measured 33 K by the extrapolation approach similar to that of Yun et al [16] but arrived at a very different conclusion that 33 K of pure CB7CB is monotonically increasing as the sample is cooled down.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations